Estimating floodwater depth using SAR-derived flood inundation maps and geomorphic model in kosi river basin (India). Issue 15 (22nd August 2022) - Parida, Bikash Ranjan; Tripathi, Gaurav; Pandey, Arvind Chandra; Kumar, Amit
Abstract: Flooding is the most widespread and frequent natural disaster in developing countries. Until recent years, determining flood extent and inundation depth were undertaken using hydrodynamic models but have pertinence constraints in data-scarce regions. This has given the new potential to characterize floods (e.g., inundation, depth, duration) at a large-scale using a geomorphic approach. The SAR data was employed to derive flood extent and the 12.5 m resolution DEM-based geomorphic method was applied to determine inundation depth in flooded domains of Kosi River Basin (KRB) in North Bihar (India) to characterize 2017 floods. The total inundated area in flooded domains over KRB was estimated at 4, 108.2 km 2 (20.88%). Most of the area (2, 750 km 2, 14%) of flooded domains over land had a water depth of 0.1 to 1 m. The geomorphic approach is appropriate for characterizing floods over large-scale and data-sparse basins like KRB and afforded a new horizon for flood risk assessment on flood vulnerable areas.